2003
DOI: 10.1016/s0006-3495(03)74856-5
|View full text |Cite
|
Sign up to set email alerts
|

Confined Diffusion Without Fences of a G-Protein-Coupled Receptor as Revealed by Single Particle Tracking

Abstract: Single particle tracking is a powerful tool for probing the organization and dynamics of the plasma membrane constituents. We used this technique to study the micro -opioid receptor belonging to the large family of the G-protein-coupled receptors involved with other partners in a signal transduction pathway. The specific labeling of the receptor coupled to a T7-tag at its N-terminus, stably expressed in fibroblastic cells, was achieved by colloidal gold coupled to a monoclonal anti T7-tag antibody. The lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
217
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(236 citation statements)
references
References 42 publications
(52 reference statements)
17
217
0
2
Order By: Relevance
“…For instance, Kusumi's group determined that phospholipids undergo hop diffusion in cell membrane based on the control experiments that modified or depleted membrane skeleton (100). On the other hand, Salome's group believed that a G-protein-coupled receptor follows cage diffusion based on their visual inspection of the trajectories-only few hops from one domain to another were observed (69). With a close examination, our results resemble the hop diffusion described by Kusumi based on 40 nm gold particle tracking (Fig.…”
Section: Challenges In Molecular Trajectory Analysissupporting
confidence: 74%
See 3 more Smart Citations
“…For instance, Kusumi's group determined that phospholipids undergo hop diffusion in cell membrane based on the control experiments that modified or depleted membrane skeleton (100). On the other hand, Salome's group believed that a G-protein-coupled receptor follows cage diffusion based on their visual inspection of the trajectories-only few hops from one domain to another were observed (69). With a close examination, our results resemble the hop diffusion described by Kusumi based on 40 nm gold particle tracking (Fig.…”
Section: Challenges In Molecular Trajectory Analysissupporting
confidence: 74%
“…S8 for discussion on various types of confined diffusion). Although the exact expression of MSD depends on the shape of the confining region and on spatial dimensionality, the two-dimensional (2D) MSD of confined diffusion can be approximated by (39,69) MSD 2D ðtÞy L 2 3…”
Section: Extracting Dynamic Parameters From Msdmentioning
confidence: 99%
See 2 more Smart Citations
“…In the work performed on the μ opioid receptor, it was also observed that the macroscopic diffusion coefficient, D M , is correlated to L 2 : D M ∼ L 2 . The detection of jumps by a new algorithm (see "Appendix 1") showed that the trajectories do not display enough jumps over actinlike barriers to account for the observed relationship [48].An alternative mechanism known as "interacting Brownian particle" model was proposed to explain the observed diffusion behaviours [15]. It stated that attractive longrange interactions can be sufficiently strong to ensure the stability of small confined assemblies of proteins without invoking external barriers (see Fig.…”
mentioning
confidence: 99%